THE PERFORMANCE COMPARISON OF AI TOOLS IN COGNITIVE DEVELOPMENT - Aqib Ali Buriro,; Jawad Hussain Awan,; Khalid Charan,; Sameer Hashmat Qazi,; Raheel Sarwar, (Spectrum of Engineering Sciences, 2025)
This paper discusses the growing concern about Artificial Intelligence tools, that having inadequate ability to improve cognitive growth and creative project work. Even though ChatGPT and Gemini are widely used, these platforms frequently fall short in understanding the nuances and complexity of human reasoning. They lack the intuitive comprehension required for abstract or context-rich queries and instead rely on formal cues. Because of this, users might grow unduly reliant on AI, which would impair their ability to think critically and creatively, particularly in professional and academic contexts. Furthermore, gathering vast amounts of data sometimes without explicit user consent is a common step in the creation of AI systems. The risks of unlawful data use for manipulation and behavioral impact are highlighted by previous reported events, such as disputes involving large internet companies like Facebook. Despite the fact that some AI tools make the claim to mimic emotional intelligence, their limitations originate from the fact that they are human-made, subject to biases, and have the capacity to spread false information that is frequently influenced by big corporate interests. Concerns regarding AI's legitimacy in academic settings are also raised by the dearth of trustworthy sources and the technology's propensity to generate erroneous or mixed content.